LEGAL PROTECTION OF WOMEN WORKERS IN THE INDUSTRIAL ERA 5.0 - Ginting, Grenaldo; Hady, Sultan; Hamid, Helson (PT. Altin Riset Publishing, 2024)
Objective study This is for analysing legal protection for female workers in the industrial era 5.0. The method used is a qualitative method study with type study studies as references. Types of studies References used for digging deep understanding about a topic or phenomenon with an analysis of literature and where are the relevant sources? in study This relates to legal protection for female workers in the Industrial Era 5.0. As for the data, it was obtained through study and analysis of various references, like journal books, scientific articles, and documents related to the topic being researched. Then, the researcher found an interesting thread in red. Finally, draw conclusions based on the results, findings, and study. Results study This leads to the conclusion that protection laws for workers and women both within and outside of the country become the primary focus of guard supremacy laws in various countries. Protection for working women can be significantly improved by implementing strong policies, enforcing strict regulations, and taking active roles from the government, international organisations, and society. In the Industry 5.0 era, protection laws for women need adaptation to the dynamics just brought by technology. Comprehensive regulations and implementation technology For detection early, education, encouraging gender equality, cooperation between government and private sector, as well as enforcement of strong laws, become elements important in ensuring effective protection for women in the environment.